Physicochemical and functional characteristics of black potato (Coleus tuberosus) flour from some locations in East Java Indonesia - Jhauharotul Muchlisyiyah; Teti Estiasih; Dita Puspa Arinta; Hera Sisca Prasmita (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Coleus tuberous (local name: kentang hitam/black potato) is widely available in Indonesia. Commonly, black potatoes are only boiled and made into side dishes. Black potatoes have the potential to be the ingredient of functional foods. However, black potatoes can only be harvested once a year. Therefore, a low moisture form (flour) storage is required for longer shelf life. Research on physicochemical and functional characteristics of black potato flour is expected to widen the use of black potato flour as raw materials in various food products. This study was aimed to analyze the chemical, physical, and functional  characteristics of black potato flour originating from Sunthi (Jaten), Begal, and Kopenan Forest villages in East Java, Indonesia. All the measurements were carried out with three replications and analyzed using one-way ANOVA, then followed by the Tukey test to find the difference from each sample at a 0.05 significance level. The correlation analysis and principal component analysis were also subjected to study the relationship between each character of the samples. The result indicated that the tuber and starch have relatively high ash, amylose, and total phenol concentration. Several high correlations were found between the characteristics of the black potato flours. One of the high correlations was the water absorption index with starch, amylose, and total phenolic content. The principal component analysis (PCA) also found that the three samples were loading differently in the score plot. Two first principal components (PCs) were the contributing factor for 100% of the differences.